Carbon Stock Potential of Mangrove Species in South Lombok Coastal Ecotourism Area - Luthfiyannisa Luthfiyannisa; Agil Al Idrus; Abdul Syukur; Lalu Zulkifli (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Data on carbon stocks in mangroves within coastal ecotourism areas remain limited, despite their high potential as tropical blue carbon sinks. This study evaluates the carbon stock potential of mangrove species at Bale Mangrove Ecotourism Site using line transect-quadrat plot methods and IPCC guidelines, incorporating allometric biomass analysis (V = π(d/2)²th with genus-specific wood density). Key findings reveal total aboveground biomass of 22.95 ton/ha and carbon stock potential of 11.48 ton C/ha (equivalent to 42.12 ton CO₂/ha), dominated by Rhizophora mucronata (3.96 ton C/ha) due to larger stand size and high wood density (0.92 g/cm³), while Avicennia marina was lowest (0.06 ton C/ha) owing to minimal abundance. These inter-species differences reflect early dynamics where pioneer Rhizophora excels in initial biomass accumulation. Overall, results confirm mangrove restoration's role in IPCC-based carbon inventories, with implications for sustainable ecotourism management to maximize long-term blue carbon capacity